Workplace-based assessments: The right time to start - Dilnawaz, Mansoor; Shaikh, Zafar Iqbal; Mazhar, Hina; Iftikhar, Nadia; Akhtar, Aisha; Sadiq, Sakina (Journal of Pakistan Association of Dermatologists, 2016)
Workplace-based assessments (WPBAs) refer to the assessment of working practices based on what doctors actually do in the workplace and is predominantly carried out in the workplace itself (PMETB, 2007). WPBAs should be recognized as a series of essential educational events along a learning trajectory. WPBAs are an essential part of an assessment system alongside traditional examinations. The primary purpose of WPBAs is to provide constructive feedback to the trainees. The trainer is required to identify trainees not progressing along their structured learning plan so that early remedial action can be initiated. An understanding of the acceptable level of clinical competence required for a particular stage of learning is essential. This will ensure that the patients are safe during training through appropriate supervision and assessment. Stakeholders (trainers, trainees, managers, patients) should actively be involved in the development and implementation of the programme to ensure transparency and understanding of the process. Â